2008
DOI: 10.21273/hortsci.43.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Management, Survival Strategies, and Host Range of Colletotrichum acutatum on Strawberry

Abstract: Colletotrichum spp. are broad-range pathogens, meaning that many species can infect a single host and a single species can infect diverse hosts. For example, Colletotrichum acutatum J.H. Simmonds affects a wide range of crops, causing disease symptoms on apple, almond, anemone, citrus, lupin, peach, pecan, strawberry, and others, whereas Colletotrichum gloeosporioides Penz. (Penz. & Sacc.) can affect many of the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 28 publications
2
13
0
5
Order By: Relevance
“…However, several species from the C. gloeosporioides species complex can be responsible for anthracnose in these crops. Likewise, Freeman () discussed the host range of several Colletotrichum species that are now known to comprise more than one, sometimes even dozens, of evolutionary different lineages. Despite this, recent studies have reported that strains belonging to the same Colletotrichum species are able to infect different hosts.…”
Section: Discussionmentioning
confidence: 99%
“…However, several species from the C. gloeosporioides species complex can be responsible for anthracnose in these crops. Likewise, Freeman () discussed the host range of several Colletotrichum species that are now known to comprise more than one, sometimes even dozens, of evolutionary different lineages. Despite this, recent studies have reported that strains belonging to the same Colletotrichum species are able to infect different hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Although the life cycle of G. uvicola on grapevines is believed to involve infection via the pedicel in spring (Longland and Sutton 2008), the importance of flower infections and implications for disease management have not been studied previously. C. acutatum infects both vegetative and reproductive tissues, including the flowers of a wide range of host plants (Freeman 2008;Peres et al 2008), the susceptibility of V. vinifera inflorescences to C. acutatum however has not been documented previously. We demonstrate here that glasshouse-grown (cv Chardonnay) and fieldgrown (cv Shiraz) grapevine inflorescences are susceptible to infection by C. acutatum and G. uvicola.…”
Section: Discussionmentioning
confidence: 99%
“…While detached fruit of host plants other than grapes have been shown to be susceptible to G. uvicola (Ridings and Clayton 1970), the fungus is not known to cause problems on horticultural plants other than grapes. In contrast C. acutatum has a wide host range causing anthracnose on a range of fruit crops (Freeman 2008;Prusky et al 2000) and flower infection in citrus (Peres et al 2008). The life cycles of both fungi on grapevines have largely been studied in Muscadinia rotundifolia (syn.…”
Section: Introductionmentioning
confidence: 99%
“…1. B) (Freeman et al, 1998;Cao et al, 2017), , , , (Freeman, 2008;Than, 2008;Nam et al, 2014;Lim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%